1975
DOI: 10.1159/000122394
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Stress on Catecholamines and Tyrosine Hydroxylase Activity of Individual Hypothalamic Nuclei

Abstract: The effects of acute stress on norepinephrine (NE) and dopamine (DA) concentrations and of repeated stress on tyrosine hydroxylase (TH) activity were measured in individual hypothalamic nuclei and other rat brain regions. A microdissection technique and radioisotopic enzymatic assays enabled these studies to be performed. NE and DA concentrations were reduced and TH activity increased selectively in the arcuate nucleus. These results suggest that the arcuate nucleus may be selectively involved in the stress re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
29
0

Year Published

1976
1976
2001
2001

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 11 publications
5
29
0
Order By: Relevance
“…These results support many earlier studies of an involvement of catecholamines in stress reactions as measured with biochemical and histochemical (formaldehyde fluorescence) methods. Thus acute and/or chronic stress has been shown to affect norepinephrine (36)(37)(38)(39)(40)(41)(42)(43)(44)(45), epinephrine (46)(47)(48), and catecholamine-synthesizing enzymes (45)(46)(47)(48)(49)(50)(51). In agreement, both norepinephrine and epinephrine medullary neurons have been shown to contain the glucocorticoid receptor (52).…”
Section: Discussionmentioning
confidence: 81%
“…These results support many earlier studies of an involvement of catecholamines in stress reactions as measured with biochemical and histochemical (formaldehyde fluorescence) methods. Thus acute and/or chronic stress has been shown to affect norepinephrine (36)(37)(38)(39)(40)(41)(42)(43)(44)(45), epinephrine (46)(47)(48), and catecholamine-synthesizing enzymes (45)(46)(47)(48)(49)(50)(51). In agreement, both norepinephrine and epinephrine medullary neurons have been shown to contain the glucocorticoid receptor (52).…”
Section: Discussionmentioning
confidence: 81%
“…Since it has been reported that exposure to cold for several hours will decrease the concentration of CA in the ANA [Palkovits et al, 1975], we measured synthesis rates in the ANA after 3 h of cold exposure. In contrast to our results after 30 min of cold ( fig.…”
Section: Resultsmentioning
confidence: 99%
“…Further studies are therefore necessary in order to determine the relative contribution made by changes in synthesis and/or release of NA and to correlate these changes with alterations in hypothalamo-pituitary adrenal activity. In the light of the recent findings of Palkovits, Kobayashi, Kizer, Jacobowitz & Kopin (1975) who demonstrated that the CA content of the arcuate nucleus was selectively depleted after exposure to three different types of acute stress (i.e. formalin, immobilization and exposure to cold), it would also be of interest to determine whether the decrease in hypothalamic NA observed after ether stress is localized in this hypothalamic nucleus.…”
Section: Discussionmentioning
confidence: 99%